KAJIAN CARA PENJEMURAN TERHADAP MUTU BIJI KEDELAI - Ratna Wylis Arief; Dewi Rumbaina Mustikawati (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2008)
Drying of soybean plants have some problems, because its volume is big and so needed big place to drying. Generally, the farmers drying their soybeans with traditional methode with energy of sunrise or aeration without cover and it caused high losses and persentage of waste. The experiment was conducted at Kalirejo Subdistrict, Central Lampung residence on June 2004. The teratments is drying methode such as: on the ground without cover (J1); on the floor without cover (J2); on the ground with cover (J3); on the floor with cover (J4); piled on the floor (J5); and roll back on the floor (J6) with 3 replications. Parameters of observation were persentage of filled out seed, broken seed, grapeseed, and waste. Analyze of data with DMRT at 5% level. The result showed that the soybean dried with cover on the ground and on the floor has highest persentage of filled out seed and lowest waste; the soybean that dried with piled on the floor has highest persentage of broken seed; and drying methode did not influenced on the grapeseed. Key words: soybean, drying, quality